Ophthalmologic problems correlates with cognitive impairment in patients with Parkinson's disease - Zhang, Chao; Wu, Qian-qian; Hou, Ying; Wang, Qi; Zhang, Guang-jian; Zhao, Wen-bo; Wang, Xu; Wang, Hong; Li, Wei-guo (Frontiers in Neuroscience, 2022)
Objective: To identify the relationship between visual dysfunction and cognitive impairment in Parkinson’s Disease (PD) older than 50 years, set up an useful nomogram for predicting the risk of cognitive impairment during the disease progression. Methods: A total of 205 Parkinson’s patients (age >50) and 200 age-matched controls completed the Visual Impairment in Parkinson’s Disease Questionnaire and underwent neuro-ophthalmologic examinations, including ocular fundus photography and optical coherence tomography. We compared groups with or without visual impairment through metatranscriptomics and 16s rDNA sequencing. A nomogram based with ophthalmic events was summarized using multivariate logistic and LASSO regression and verified via bootstrap validation. Results: One or more ophthalmologic symptoms were present in 57% of Parkinson’s patients, compared with 14% of the controls (χ2 test; p<.001). The visual impairment questionnaire showed good sensitivity and specificity (area under the curve [AUC] = 0.918, p<.001) and a strong correlation with MoCA scores (Pearson r=-0.4652, p<.001). Comparing VIPD-Q scores between pre- and post-deep brain stimulation groups showed that DBS improved visual function (U test, p<.001). Thickness of the retinal nerve fiber layer and vessel percentage area correlated with MoCA scores and VIPD-Q. Metatranscriptomics and 16s rDNA sequencing indicated that PD patients with visual dysfunction usually shared similar changes in genes expression and microbiota composition with cognitive impaired group. Conclusion: The study findings provide a convincing evidence for the correlation between visual dysfunction and cognitive impairment. VIPD-Q scores, RNFL and VPA were related to cognitive deterioration in Parkinson’s disease. Genes and microbiota related to cognitive impairment enriched in PD patients with visual dysfunction.